Students' online shopping behavior: an empirical study - Delafrooz, Narges; Paim, Laily; Khatibi, Ali (Marsland Press, 2010)
The ever-increasing use of the internet in Malaysia provides a developing prospect for E-marketers. Such marketers' awareness of the factors affecting Malaysian buyers’ attitude can further develop their marketing strategies in converting potential customers into active ones, while maintaining their existent online customers. This paper sets out to examine the factors influencing students’ attitudes towards online shopping in Malaysia through a five-level Likert scale self-administered questionnaire, which was developed based on prior literature. A total of 370 students were randomly selected. The multiple regression analysis demonstrated the most significant determinants of consumers’ attitudes towards online shopping. The results indicated that utilitarian orientation, convenience, price, and a wider selection influenced consumers’ attitudes towards online shopping. Therefore, e-retailers should emphasize a more user-friendly function in order to provide utilitarian customers a way to find what they need efficiently.